PENGARUH PEMBERIAN INSENTIF TERHADAP PENINGKATAN SEMANGAT KERJA KARYAWAN PADA PT. ASTRA INTERNASIONAL Tbk- DAIHATSU CABANG PEKANBARU (Kasus Karyawan Bagian Marketing Produk Mobil Daihatsu) - Syarifah Aini; Lena Farida (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Riau, 2015)
The problem in this research is the system of incentives is considered employees of the marketing is not in their favor. This of course affects employee morale in the work and will impact on the achievement of corporate goals. The purpose of the study was to determine and analyze incentives and employee morale as well as determine the effect of incentives on semagat employee marketing division at PT. Astra International Tbk-Daihatsu Branch Pekanbaru. The study concluded that giving incentives to employees in the marketing division of PT. Astra International Tbk-Daihatsu Pekanbaru branch overall result is good. But there are still many shortcomings in the implementation of the provision of incentives, including the incentive eligibility still too small and too concerning provisions in the granting of incentives designed not to benefit the employee marketing division. Employee morale in the marketing division of PT. Astra International Tbk-Daihatsu Pekanbaru branch as a whole is considered quite good. This is due to the lack of cooperation and willingness to help each other among fellow employees. Besides the lack of discipline of employees, which employees work outside of the ways that have been set by the company and the attitude of the employees in the work that is still not good, as well as the attitude of the employees who are not concerned with the problems faced by other employees. Analysis with SPSS, showed that the relationship between employee morale (dependent variable) with Incentives (independent variables) have a strong degree of correlation, which means that any additions or enhancements to existing incentives will lead to improvements to employee morale.Keywords : Incentives, morale, PT. Astra International Tbk-Daihatsu Branch Pekanbaru.